Knowledge Management and Organisational Resilience of Pre-Shipment Inspection Companies in South South, Nigeria - Sede, Thomas A.; Okoisama, Thomas C.; Bagshaw, Karibo B. (Research Parks Publishers, 2023)
The study examined the nexus between knowledge management (dimensioned by knowledge sharing and knowledge storage) and organisational resilience (measured by adaptability) of pre-shipment inspection companies in South-South, Nigeria. The upper echelons theory underpinned the study, while the underlying philosophy is positivism. The cross-sectional survey was adopted in generating primary data through the use of questionnaire. The elements of the accessible population are the 480 middle and top-level managers of all the 20 Pre-Shipment Inspection Companies, in South-South, Nigeria, and a sample size of 235 respondents was determine. The hypotheses were tested at 0.05 significance level, using partial least square-structural equation modeling. The study concludes that when management increases the adoption of knowledge management, the tendency for organisational resilience will be enhanced. It is therefore recommended that managers of Pre-Shipment Inspection companies in South South, Nigeria, should enhance the implementation of knowledge sharing in order to bring about adaptability of the organisation. This can be achieved by conducting regular meetings to exchange experiences, using newsletters to disseminate information and ensuring knowledgeable staff share their ideas with other staff. Moreso, Management of Pre-Shipment Inspection companies in South-South, Nigeria, should improve their knowledge storage practices as a means of increasing the level of adaptability in the organisations. This can be achieved by having a system for keeping and retrieving information, ensuring staff have access to required information.